The Relationship Between Strategic Supply Chain Integration and Performance: A Meta‐Analytic Evaluation and Implications for Supply Chain Management Research. Issue 1 (March 2014) - Mackelprang, Alan W.; Robinson, Jessica L.; Bernardes, Ednilson; Webb, G. Scott
<x xml:space="preserve">Abstract</x> Although research evaluating the impact of supply chain integration on performance has advanced substantially in the last decade, inconsistency and considerable variability of empirical findings leave unanswered questions for both research and practice. Using a meta‐analysis, we examine empirical studies to clarify the actual relationship, suggest new directions, and ultimately contribute toward the development of supply chain management theory. We focus on "strategic" supply chain integration rather than on functional or operational/tactical studies, which would weaken the practical value of the analysis and findings. To ascertain focus and homogeneity of the sample, we adopt a rigorous search protocol and sample construction. We find that integration–performance relationships are complex and nuanced such that integration should not be universally viewed as improving performance. We identify relationships that are more generalizable and also those that need additional scrutiny. Finally, we discuss the implications of our findings and provide directions for future research.